2022
DOI: 10.3390/app12136456
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Hybrid Flow-Shop Scheduling under Time-of-Use and Ladder Electricity Tariffs

Abstract: With the increasing influence of climate change, green development has become an important trend. Since manufacturing represents approximately one-half of total energy consumption, reducing the amount of energy consumed within this industry is imperative. This study provides a hybrid flow shop scheduling issue under a time-of-use and ladder electricity price system to reduce total energy consumption without compromising maximum completion time. An improved non-dominated sorting genetic algorithm II with some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Most of them were published in the years 2018-2022. Among them, several articles [32,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] were dedicated to the application of NSGA and its variations to the DFSP in green scheduling manufacturing. Optimization objectives are the minimization of the makespan and the Total Energy Consumption (TEC) and/or carbon emissions [12].…”
Section: Green Scheduling Problems Application Areasmentioning
confidence: 99%
“…Most of them were published in the years 2018-2022. Among them, several articles [32,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] were dedicated to the application of NSGA and its variations to the DFSP in green scheduling manufacturing. Optimization objectives are the minimization of the makespan and the Total Energy Consumption (TEC) and/or carbon emissions [12].…”
Section: Green Scheduling Problems Application Areasmentioning
confidence: 99%
“…Schulz et al [25] considered a hybrid flow shop scheduling problem, aiming to minimize both energy cost and total tardiness. Chen et al [26] developed an improved non-dominated sorting genetic algorithm II for the hybrid flow shop scheduling problem under time-of-use. Wang et al [27] addressed the two-machine permutation flow shop scheduling problem with the objective of minimizing the total electrical cost under time-of-use electricity pricing.…”
Section: Introductionmentioning
confidence: 99%
“…The redundancy of the machines used may enable dealing with jobs flexibly and avoid bottlenecks [2]. In recent decades, HFSPs have been extensively investigated and a number of results have been obtained [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al [8] designed a hybrid Pareto spider monkey optimisation algorithm for solving problems, minimizing the total energy consumption and total time taken. Chen et al [9] reported an improved NSGA-II including optimization strategies. Qin et al [10] presented a mathematical model of a blocking EHFSP and proposed a modified iterative greedy algorithm based on a swap strategy.…”
Section: Introductionmentioning
confidence: 99%